The Effect of Virtual Rehabilitation Added to an Accelerated Rehabilitation Program After Anterior Cruciate Ligament Reconstruction: A Randomized Controlled Trial - POLAT, MİNE GÜLDEN; KURU ÇOLAK, TUĞBA; KARAKOÇ, ZEHRA BETÜL; SARI, ZÜBEYİR (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: This study aimed to determine the effectiveness of virtual rehabilitation on balance and functionality in patients with anterior cruciate ligament (ACL) reconstruction. Methods: A total of 22 males who had undergone ACL reconstruction were divided into Nintendo and control groups. Both of the groups received six week accelerated rehabilitation in our department, and the Nintendo Wii(C) (Nintendo, Washington, USA) balance games were added to Nintendo group after three weeks for forty minutes a day, three times a week. Patients were evaluated for pain (visual analog scale), functionality (Lower Extremity Functional Scale), center of gravity (COG) and balance (Nintendo Wii(C)) at the baseline and end of the 3th and 6th week of rehabilitation program. Results: Similar improvements were determined in the pain, functionality, COG and balance scores of the two groups at the end of the treatment program and there were no significant differences between the groups in the amount of change in all parameters (p= 0.256, 0.393, 0.707, 1.000). Conclusion: According to the results of this study the Nintendo Wii(C) balance games applied in the clinic under physiotherapist supervision did not change the outcome of the rehabilitation in early period after ACL reconstruction.
Keywords: Anterior Cruciate Ligament; Nintendo Wii (c); Postural Balance; POSTURAL CONTROL; MOTOR CONTROL; KNEE PAIN; FOLLOW-UP; BALANCE; PROPRIOCEPTION; RELIABILITY; EXERCISES; INJURY; STABILITY